2018
DOI: 10.1002/cae.21898
|View full text |Cite
|
Sign up to set email alerts
|

An MS excel add‐in for teaching hydraulics of pipe flow in engineering curricula

Abstract: This paper presents implementation of an MS Excel add‐in incorporating Visual Basic for Applications for teaching pipe flow calculations in undergraduate and graduate level. The add‐in contains a total of 108 functions for several purposes ranging from continuity equation to branching pipes and pipe network problems. Tip texts and a number of userforms were developed for easy use of the tool. A user's guide was also prepared that includes the theory of hydraulic calculations and numerical methods involved. Bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…As the Excel spreadsheet and its built‐in environment for coding (VBA) have been successfully utilized for implementing many engineering problems [1,4‐7,11,13,14,17,21,22,28,30,31], they may be considered a useful tool for comprehensive application to predict resistance grain and form roughness coefficients. In this regard, the spreadsheet developed in this study, which may be found at https://www.dropbox.com/s/0fvl1pdtl6n64ni/estimation.rar?dl=0, has four worksheets, which arev as follows. The notation worksheet: In the first worksheet, all BRPs and the corresponding input and output parameters are introduced, as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…As the Excel spreadsheet and its built‐in environment for coding (VBA) have been successfully utilized for implementing many engineering problems [1,4‐7,11,13,14,17,21,22,28,30,31], they may be considered a useful tool for comprehensive application to predict resistance grain and form roughness coefficients. In this regard, the spreadsheet developed in this study, which may be found at https://www.dropbox.com/s/0fvl1pdtl6n64ni/estimation.rar?dl=0, has four worksheets, which arev as follows. The notation worksheet: In the first worksheet, all BRPs and the corresponding input and output parameters are introduced, as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Under turbulent conditions, i.e. Re ≥ 4000, explicit Swamee-Jain formula (Eqn 2b) was employed [21].…”
Section: Hydraulicsmentioning
confidence: 99%
“…In any case, learning the operating aspects of WDNs could be possible while mathematical background of WDN design problems is overlooked [6]. In the last few years, the instructors realized the importance of mathematical aspects of the design problem and started to develop their own methods of teaching the mathematical background of WDN design [19][20][21]. The motivation for this study comes from the need of easily teaching the mathematical background of WDN design problems.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, many scholars have studied the characteristics of ows which come from the intersection of ssure-ssure or ssure-conduit. When groundwater ows in the conduit with ssures, in addition to the local head loss at the intersecting point, the existence of ssure will also a ect the ow of the stream in the conduit, resulting in a head loss along the conduit itself [6][7][8]. It is necessary to take the above-given two factors into account when calculating the converted permeability coe cient of the karst conduit, especially when there are many ssures intersecting along the conduit [9,10].…”
Section: Introductionmentioning
confidence: 99%